Implementation of Virtual Private Server (VPS) Using Digital Ocean Cloud Server on BMT. Mentari East Lampung - Arif Hidayat; Danang Prabowo (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
The presence of cloud technology at this time is considered very necessary to be implemented at BMT Mentari East Lampung. In the implementation of the fund or financial management activities, BMT Mentari East Lampung, already has the support of an Information Technology network to support daily operational activities, in addition to that, some have even implemented internet and intranet technology both at the central and branch levels. The strength factor that emerged was the great desire of BMT Mentari Lampung managers to implement VPS using DigitalOcean's Cloud Server so that all databases currently using were neutralized on 1 public computer or cloud. By using VPS services, BMT Mentari has full control over the server and all its settings on the DigitalOcean Cloud Server and VPS security is more guaranteed than previous intranet services. It should be noted that the manager of BMT Mentari East Lampung can adjust the VPS security configuration according to the required standards and the disk space and bandwidth in VPS services are safer and more stable.